Psychological Well-Being and Student Academic Burnout - Indreswari, Henny; Probowati, Devy; Rachmawati, Indriyana (Jurnal Kajian Bimbingan dan Konseling, 2022)
Psychological well-being is an important aspect for students that needs to be considered in the current situation, which in fact many are faced with academic burnout. This research was conducted with the aim of knowing the relationship between psychological well-being and student academic burnout. The research design used is correlation, with a research sample of 180 students. The sampling technique used is proportional random sampling. Collecting data using psychological well-being scale and academic burnout scale. The data analysis technique used is Pearson's product moment. The results showed that psychological well-being has a negative relationship with academic burnout. This means that the higher the psychological well-being of students, the lower their academic burnout. These findings can be used as a basis for universities to provide mental health services needed by students and lecturers needed to assist students in providing guidance and counseling services.